2000
DOI: 10.1002/1529-0131(200008)43:8<1891::aid-anr28>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in patients with connective tissue diseases treated with specific cyclooxygenase 2 inhibitors: A report of four cases

Abstract: have been approved for the treatment of osteoarthritis and rheumatoid arthritis. Unlike nonsteroidal antiinflammatory drugs, specific COX-2 inhibitors do not inhibit platelet activation. However, these agents significantly reduce systemic production of prostacyclin. As a result, theoretical concerns have been raised that specific COX-2 inhibitors could shift the hemostatic balance toward a prothrombotic state. Patients with connective tissue diseases (CTD), who may be predisposed to vasculopathy and thrombosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 13 publications
1
63
0
2
Order By: Relevance
“…26,27) The present study showed that GMGHT effectively inhibited the mRNA and protein expression of COX-2 in a dose dependent manner. It suggests that GMGHT may provide its beneficial effect on anti-inflammation.…”
Section: Discussionmentioning
confidence: 51%
“…26,27) The present study showed that GMGHT effectively inhibited the mRNA and protein expression of COX-2 in a dose dependent manner. It suggests that GMGHT may provide its beneficial effect on anti-inflammation.…”
Section: Discussionmentioning
confidence: 51%
“…Since clinical thrombosis is the summation of risk factors, small changes in prostacyclin levels, as the result of treatment with cyclooxygenase 2 antagonists in systemic lupus erythematosis patients with other risk factors for thrombosis, result in increased risk for clinical thrombosis. 45 Thus, the present investigations indicate that components of the plasma kallikrein/kinin system indirectly influence one's risk for thrombosis through its interaction with components of the renin angiotensin pathway. These findings broaden our notion of factors that modify thrombosis risk and suggest new targets for antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 59%
“…Neither disruption of PGHS-2 nor IP deletion results in spontaneous thrombosis, but, rather, both augment the response to thrombogenic stimuli. Thus, an unrelated predisposition to thrombosis would facilitate detection of a cardiovascular hazard from PGHS-2 inhibitors, as has been observed in patients (29)(30)(31).…”
Section: Discussionmentioning
confidence: 95%